(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
One of the important tasks in the educational process is to identify and develop student’s knowledge, skills, and competencies. Pedagogical assessment is an integral part of this process, as it ensures the quality and effectiveness of education. In particular, the scientific application of various assessment methods in modern education plays a significant role in increasing students’ activity and intellectual potential.